The Deceiver - Forsyth, Frederick, 1938- (India Corgi Books, 1991)
McCready, chief of Britain's Secret Intelligence Service, offered his choice of two positions--an obscure administrative job or early retirement, is not afraid to press the CIA to the explosion point to convince them their prize defector is a double agent.
Keywords: Spy stories -- Great Britain -- Intelligence service